AN ANALYTICAL STUDY OF SWITCHING TRACTION MOTORS - Bezruchenko, V. M.; Shapovalov, A. V. (Science and Transport Progress, 2010)
The analytical study of switching of the tractive engines of electric locomotives is conducted. It is found that the obtained curves of change of current of the sections commuted correspond to the theory of average rectilinear switching. By means of the proposed method it is possible on the stage of design of tractive engines to forecast the quality of switching and to correct it timely.